USHUL TAFSIR DAN TAFSIR - Latifah, Nadia; Putera, Mandala; Sholehah, Mar’atus (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Ushul Tafsir is a discipline that discusses the principles and methods of interpreting the Qur'an. This science establishes the rules that must be considered so that interpretation is carried out accurately and in accordance with the context. Some of the topics discussed in ushul tafsir include the meaning of the Arabic language, the historical context of the verses, and the general rules of understanding the text. Research Methods Using descriptive with qualitative approach. The results showed that Ushul-tafsir serves as a foundation for interpreters to explain the meaning contained in the Qur'an to maintain the integrity of the text and avoid misinterpretation. Tafsir, on the other hand, is the result or product of the process of interpreting the Qur'an. Tafsir can be divided into several types, such as tafsir bil ma'tsur (based on history) and tafsir bil ra'y (based on reason and logic). Tafsir can also contain different approaches, such as linguistic interpretation, thematic interpretation, and contextual interpretation. Each type of tafsir offers a different perspective on the verses of the Qur'an, resulting in a rich and deep understanding. Both ushul tafsir and tafsir complement each other and contribute to a global understanding of the Muslim holy book.